The Effectiveness of Making and Collection of Family Albums on Autobiographical memory and Happiness in Elderly - Masomeh Zabeti Arani; Anahita Khodabakhshi-Kolaee (Mashhad University of Medical Sciences, 2017)
Background and objective: Aging is a sensitive period of human life and attention to the problems and needs of this stage is a social necessity. Among the common problems in this period, insufficiency in their memory performance and lack of happiness due to lack of social activities .Therefore, the aim of current research is to evaluate the effectiveness of making and collection of family albums on autobiographical memory and happiness in elderly. Methods:The current study is a semi-experimental study with pre-test and post-test with group control. The population of study was old employees who are member of Retirement organization of Tehran Municipality during2015-2016. 30 older selected based on the inclusion criteria  and they were randomly assigned to the control (n= 15) and experimental group (n=15).The experimental group received techniques of making and collection of family photo albums for 10 session (90 minutes,one session per week). The research instruments were Mini Mental State Examination(M.M.S.E),Oxford Happiness Inventory (OHI) and Autobiography Memory Interview (AMI). For Statistical analysis used analysis of covariance and data was analyzed by SPSS software 23 version. Results: The finding of the covariance analysis indicated that there is a significantly difference in scores of autobiographical memory among older adults in pre and post-test (p